Work Efficiency Through Systems: A Study of Tourplan Access in Discova's Customer Experience Team - Ni Komang Putri Widiantari; Made Artajaya; I Gede Ngurah Primanda S Rahadiarta (Politeknik Pariwisata Bali, 2025)
This study aims to examine how limited system access impacts employee work efficiency in the Customer Experience Department of Discova travel agency. Along with the increasing demand for fast and precise customer service, limited access to systems TourPlan and other supporting platforms is a significant obstacle in daily operations. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, literature studies, and documentation. The results showed that technical constraints such as log in limitations, non-user-friendly systems, and slow system performance, directly reduce productivity and customer service quality. In addition, non-technical factors such as team communication and work culture also affect overall efficiency. As a solution, optimization of the system infrastructure is required, including increased log in capacity, system integration, and periodic training for employees. This research provides strategic recommendations to improve work efficiency through technical improvements and human resource competency development in order to support superior service quality in the travel agency industry.